Multiple Origins of Extracellular DNA Traps - Ramos-Martínez, Edgar; Hernández-González, Leticia; Ramos-Martínez, Iván; Pérez-Campos Mayoral, Laura; López-Cortés, Georgina I.; Pérez-Campos, Eduardo; Mayoral Andrade, Gabriel; Hernández-Huerta, María Teresa; José, Marco V. (Frontiers in Immunology, 2021)
Extracellular DNA traps (ETs) are evolutionarily conserved antimicrobial mechanisms present in protozoa, plants, and animals. In this review, we compare their similarities in species of different taxa, and put forward the hypothesis that ETs have multiple origins. Our results are consistent with a process of evolutionary convergence in multicellular organisms through the application of a congruency test. Furthermore, we discuss why multicellularity is related to the presence of a mechanism initiating the formation of ETs.